THE EFFECT OF VOLUME FRACTION AND FIBER LENGTH ON THE TENSILE AND IMPACT STRENGTH OF SILK FIBER REINFORCED COMPOSITES - sinarep, Sinarep; Muhamad, Ardani; salman, Salman; Saefuloh, Iman; Achmad, Zainuri (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
Material engineering technology every year always makes new breakthroughs in creating high-quality materials and have an adequate contribution. Natural fiber reinforced composite material is one of the materials currently used as fillers in composite products. Composite with natural income also has a variety of advantages offered, namely low prices and abundant availability. This study discusses the fraction of fiber volume and fiber length on the tensile strength and impact of fiber reinforced silk fibers (Samia chynthia rucini). In this study the volume fractions of fiber used were 10%, 15% and 20% with a fiber length of 10 mm and 50 mm using an epoxy resin matrix. From the composite tensile test results prove the increase in tensile strength obtained increases the volume of silk fiber in the composite. 20% with a fiber length of 10 mm is 6.859 MPa, while the lowest tensile strength value in composites with a fiber volume fraction of 0% is 1.653 MPa. The impact test shows the strength of 10% fiber volume fraction composite with 10 mm fiber length that is 0.54535 J/mm2, while the lowest impact strength value is 0% fiber volume fraction composite that is 0.50686 J/mm2.